Design and methodology of a cluster randomized factorial trial to optimize implementation strategies for the Healthy School Recognized Campus initiative - Szeszulski, Jacob; Schaefers, Allyson; De Mello, Gabrielli T.; Gardner, Julie; George, Alisha; MacMillan Uribe, Alexandra; Rethorst, Chad D.; Seguin-Fowler, Rebecca A.; Xin, Lucy (Frontiers in Public Health, 2025)
BackgroundThe Healthy School Recognized Campus initiative bundles multiple school- and research-based programs for children and adults to improve physical activity and nutrition outcomes that affect cardiovascular disease risk. This study aims to test the individual and combined impact of three implementation strategies on implementation and effectiveness outcomes.MethodsUsing the Multiphase Optimization STrategy (MOST) framework and a cluster randomized full factorial study design, two cohorts (n = 8; n = 16 total) of public elementary schools in North and East Texas will be randomized to receive combinations of the three implementation strategies – additional resources, school-to-school mentoring, and enhanced engagement – over one academic year. We will survey program implementers (e.g., Extension agents, school staff, administrators) to determine the dose of the Healthy School Recognized Campus initiative that each student receives. We will objectively measure changes in students’ MetS risk, cardiovascular fitness measured via the Progressive Aerobic Cardiovascular Endurance Run, dermal carotenoids (an estimate of fruit and vegetable intake) measured via the Veggie Meter, and body mass index pre- and post-intervention. The individual and combined (e.g., synergistic, antagonistic) impact of strategies will be evaluated after each cohort using a general linear model framework, and strategies will be modified and prepared for testing in a future randomized controlled trial.DiscussionBy using rigorous implementation science frameworks, developing three implementation strategies, and evaluating implementation and effectiveness outcomes, this study aims to determine which implementation strategy or combination of strategies have the biggest impact on the Healthy School Recognized Campus initiative.Trial registrationRegistered at clinicaltrials.gov on August 2nd, 2023 (NCT05977959).